2019
DOI: 10.1088/1361-6420/ab2aa7
|View full text |Cite
|
Sign up to set email alerts
|

Variance-stabilization-based compressive inversion under Poisson or Poisson–Gaussian noise with analytical bounds

Abstract: Most existing bounds for signal reconstruction from compressive measurements make the assumption of additive signal-independent noise. However in many compressive imaging systems, the noise statistics are more accurately represented by Poisson or Poisson-Gaussian noise models. In this paper, we derive upper bounds for signal reconstruction error from compressive measurements which are corrupted by Poisson or Poisson-Gaussian noise. The features of our bounds are as follows: (1) The bounds are derived for a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…4, the expected value of R(y, Ax) := log y − log Ax 2 should be close to σ log(1 + q) √ m. Moreover, its variance is quite small and independent of m. Hence, as per the discrepancy principle, we seek to find λ ∈ Λ such that |R(y, A xλ )−σ log(1+q) √ m| is minimized. Previous work in [18] has employed such a technique in the context of image deblurring under Poisson-Gaussian noise with a square-root based data-fidelity term of the form y + 3/8 − Ax λ + 3/8 2 .…”
Section: The Non-negative Lasso (Nn-lasso)mentioning
confidence: 99%
“…4, the expected value of R(y, Ax) := log y − log Ax 2 should be close to σ log(1 + q) √ m. Moreover, its variance is quite small and independent of m. Hence, as per the discrepancy principle, we seek to find λ ∈ Λ such that |R(y, A xλ )−σ log(1+q) √ m| is minimized. Previous work in [18] has employed such a technique in the context of image deblurring under Poisson-Gaussian noise with a square-root based data-fidelity term of the form y + 3/8 − Ax λ + 3/8 2 .…”
Section: The Non-negative Lasso (Nn-lasso)mentioning
confidence: 99%
“…We fitted a convolution kernel on 8 cropped volumes, containing isolated bead images, using GENTLE (algorithm 1). The hyper-parameters of the PSF estimation model (6) were set identically to section 2.5. Figure 7 presents a comparison of the estimated FWHMs along the principal axis and Euler angles for the 8 beads, using the GENTLE method.…”
Section: Results For Psf Calibration Stepmentioning
confidence: 99%
“…However, such a noise model can be tedious to deal with numerically at large-scale, often involving minimizing a non-smooth data-fidelity term [16,79]. While this issue has been tackled in confocal microscopy [6,72,79], its exploration in MPM imaging remains scarce.…”
Section: Introductionmentioning
confidence: 99%
“…We have proved the convexity of our estimator and derived the upper performance bound, and shown that it numerically outperforms competing methods. The recent work in [3] handles compressive inversion under with Poisson-Gaussian-uniform quantization noise, a very realistic noise model in imaging systems. Extending the numerical simulations as well as the convexity proofs to handle saturation effects in conjunction with such a Poisson-Gaussian noise model is a potential avenue for future work.…”
Section: Discussionmentioning
confidence: 99%